Contrast-enhanced MRI for simultaneous evaluation of renal morphology and split renal function in living kidney donor candidates. Issue 142 (September 2021) - Krumm, Patrick; Hupka, Tanja; Haußmann, Florian; Dittmann, Helmut; Mühlbacher, Thomas; Nadalin, Silvio; Königsrainer, Alfred; Nikolaou, Konstantin; Heyne, Nils; Kramer, Ulrich; Guthoff, Martina
Abstract: Purpose: The evaluation process of potential living kidney donors focusses on renal anatomy and split renal function. This study aimed to evaluate a magnetic resonance imaging (MRI)-based approach for simultaneous evaluation of both and its impact on clinical decision making. Method: Over a 3-year period, 65 potential living kidney donors were consecutively enrolled. The MRI protocol was extended by MR-nephrography to measure split renal function. Standard DTPA-scintigraphy was used for functional comparison. Results: Split renal function showed no systematic bias between the two methods (mean difference 0.3%, p = 0.08). Both methods would have yielded the same clinical decision for donor nephrectomy in 75% of the patients. In 25 % of the patients, one method indicated a relevant side difference while the other did not, and a different clinical decision could have been made based on split renal function alone. Conclusions: MRI proved eligible for comprehensive living kidney donor evaluation and non-inferior to scintigraphy for determining split renal function. In clinical decision making, these two methods would have resulted in the same side for donor nephrectomy in a large proportion of potential donors. Whether MRN will be implemented in clinical practice depends on transplant centre infrastructure and policy.